Upaya Meningkatkan Kesiapan Belajar Statistik Melalui Pemberian Pre-Quiz Pada Mahasiswa Calon Guru SD - Juhari, Agusalim; St. Habibah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
This study aims to examine the effect of pre-quiz implementation on students' learning readiness in the Statistics course within the Elementary School Teacher Education (PGSD) program at Universitas Negeri Makassar. Using a quantitative approach, an experimental design, and data collection through weekly pre-quizzes over four weeks, the study measured the week-to-week improvement in students' learning readiness. The results indicate a significant increase in students' learning readiness, with the average pre-quiz score rising from 43.16 in Week 1 to 78.95 in Week 4. Descriptive and inferential analyses using the Paired Sample t-Test revealed a significant difference between pre-quiz scores in Week 1 and Week 4, with t-value (5.62) > t-table (1.721) and p-value = 0.000, indicating that the pre-quiz had a positive effect on improving students' learning readiness. This improvement is also reflected in the shift of students into higher readiness categories, with more students moving into the